2016
DOI: 10.2147/ott.s114230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of feature genes for smoking-related lung adenocarcinoma based on gene expression profile data

Abstract: This study aimed to identify the genes and pathways associated with smoking-related lung adenocarcinoma. Three lung adenocarcinoma associated datasets (GSE43458, GSE10072, and GSE50081), the subjects of which included smokers and nonsmokers, were downloaded to screen the differentially expressed feature genes between smokers and nonsmokers. Based on the identified feature genes, we constructed the protein–protein interaction (PPI) network and optimized feature genes using closeness centrality (CC) algorithm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…26 Previous studies reported that smoking was associated with increased mutation burdens of multiple distinct mutational signatures. [33][34][35][36][37] Significantly positive associations between smoking and M-SGCs other than MEC might indicate that smoking induces nonspecific and variable genetic alterations, leading to carcinogenesis of ADCA and SDC.…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous studies reported that smoking was associated with increased mutation burdens of multiple distinct mutational signatures. [33][34][35][36][37] Significantly positive associations between smoking and M-SGCs other than MEC might indicate that smoking induces nonspecific and variable genetic alterations, leading to carcinogenesis of ADCA and SDC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the relationship between differentially expressed genes (DEGs) and cigarette smoking. For instance, EPHA4, FGFR2, and EGFR are differentially expressed in lung cancer tissues in cigarette smokers . Additionally, the polymorphism of P73 is suggested to be highly associated with susceptibility to smoking‐related lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, EPHA4, FGFR2, and EGFR are differentially expressed in lung cancer tissues in cigarette smokers. 5 Additionally, the polymorphism of P73 is suggested to be highly associated with susceptibility to smoking-related lung cancer. 6 Moreover, transcription factors (TFs) have been identified in lung SCC.…”
Section: Introductionmentioning
confidence: 99%
“…We compared our features with other studies and [2] identified some transcriptomes to differentiate people with different smoking habits and their features on microarray data of whole blood with our features ends up with empty set. PLA2G1B of [22] is common with our features where they used microarray data of lung adenocarcinoma patients. Methylation 450K and 27K data were used in smoking related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcriptome-based studies have been reported in the literature, including the irreversible effect of tobacco [1], identifying differentially expressed genes between smokers and non-smokers [6], [7], [22] and differentiating smokers from non-smokers [20] or current smokers from others [24]. Methylation data has been used in studies to show how smoking could be identified using single [3], [5] or multiple methylation sites [35], and to infer the effects of maternal smoking on new-borns [27].…”
Section: Introductionmentioning
confidence: 99%